Vectorial hyperbody : the new extension of Selegie Art Center, Singapore - 404347 Chew, Yee Yan (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Sarjana Muda Senibina) - Universiti Teknologi Malaysia, 2004